População em situação de rua e o mundo do trabalho: (im)possibilidades de transposição da linha abissal? - Pinho, Roberta Justel do (2020)
The homeless population is characterized by the use of the street as a space for survival and housing, by extreme poverty, heterogeneity and broken/weakned family ties. Unemployment seems to contribute to this situation; thus productive inclusion is pointed out as one of the strategies for achieving autonomy, social participation and overcoming the homeless situation. The work of Boaventura de Sousa Santos constituted the theoretical support and analysis of the work, whose general objective was to understand the relationships of the homeless population and the world of work, today, through the identification and characterization of actions and experiences of productive inclusion with this population as well as their own personal and work histories. This work was a qualitative research divided into Studies 1 and 2. Study 1 was carried out with the coordinators of 13 Centros Pop (Centers of Specialized Reference for Homeless People) in the state of São Paulo, through the application of a semi-structured questionnaire, containing a protocol of personal and professional issues of the participants, questions for the characterization of the equipment and specific questions about productive inclusion. The personal, professional, and equipment data were analyzed descriptively and Thematic Analysis was used for the open questions. Study 2 was conducted with 4 users from one of the Centros Pop participating in Study 1 and it consisted of semi-structured interviews, field notes, and participant observation. The results of Study 1 showed that access to work permeates the construction of Individualized Plan of Care in most Centros Pop, with actions aimed at productive inclusion centered on referrals and registrations for training and professional qualification. Thematic Analysis identified that whether, on the one hand, work seems to have an important role in achieving autonomy and social belonging for the homeless population, on the other hand, numerous difficulties are posed, attributed or not to the subjects’ access to work, one that has been done essentially and precariously by informal means. Intersectoriality is seen as a fundamental strategy to guarantee this access, but the criteria and requirements for this inclusion tend to further exclude subjects from this scenario. In Study 2, the narratives and histories of the four participants showed that work crosses their trajectories in different ways and, although they see in formal work an expectation for resuming life projects and leaving the street, they experience concrete difficulties for this inclusion, resorting to different forms of resistance and survival in the face of unemployment. We conclude that the institutional responses to productive inclusion have been limited to professional qualification actions, focusing on individual subjects unable to guarantee access to work. The hegemonic work in modern times is incompatible with social emancipation, imposing concrete limits on the transposition of the abyssal line and requiring the creation of counter-hegemonic alternatives, based on an ecology of knowledge, which allow access to emancipatory forms of work for the populations radically excluded from it, as is the case of the homeless population.